An Unexpected Formation of Spiro Isoxazoline-Dihydrofurane Compounds from Substituted Ketofurfuryl Alcohols - Claire Cuyamendous; Mathieu Yves Laurent; Christine Saluzzo (Molecules)
Oximation of substituted ketofurfuryl alcohols in the presence of hydroxylamine hydrochloride and pyridine in ethanol as solvent led to a new class of spiro derivatives presenting a 7-methylene-1,6-dioxa-2-azaspiro [4.4] nona-2,8-diene skeleton along with, in some cases, the predictable oxime. The structures of such spiro compounds were determined by 2D NMR spectroscopy. The suggested formation of this skeleton involves an in situ oximation/dehydration/SN’ cascade reaction.